1999
DOI: 10.1021/jp984025k
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Dioxygen in n-Alkanes

Abstract: The translational diffusion constant, D, of dioxygen, O 2 , has been measured in n-alkane solutions drawn through a microcapillary by reduced pressure. The passage of O 2 through the capillary has been monitored using its UV absorption at 190 nm. Data were taken in hexane, octane, decane, dodecane, tetradecane, and hexadecane. The diffusion constants decrease as the chain length increases and are not in agreement with the Stokes-Einstein relation. The data can be fitted to D/T ) A/η p with A ) 1.27 × 10 -8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 23 publications
(34 reference statements)
8
54
0
Order By: Relevance
“…These small molecules do not follow Stokes-Einstein law, meaning that their diffusion is not inversely related to the viscosity of the solvent (44). This property was previously evidenced for O 2 diffusion in water and n-alkanes (45,46) as well as for small non-electrolyte diffusion through lipid membranes (47). For instance, the viscosity at the core of LDL is expected to be higher than at the interior of membranes, and hence more than 100-times greater than water (0.89 versus 60 -100 mPas for water (30) and membranes (48 -50), respectively).…”
Section: Discussionmentioning
confidence: 84%
“…These small molecules do not follow Stokes-Einstein law, meaning that their diffusion is not inversely related to the viscosity of the solvent (44). This property was previously evidenced for O 2 diffusion in water and n-alkanes (45,46) as well as for small non-electrolyte diffusion through lipid membranes (47). For instance, the viscosity at the core of LDL is expected to be higher than at the interior of membranes, and hence more than 100-times greater than water (0.89 versus 60 -100 mPas for water (30) and membranes (48 -50), respectively).…”
Section: Discussionmentioning
confidence: 84%
“…Except for macromolecules, however, numerous experimental studies 3,[57][58][59][60][61][62][63][64][65][66] have shown that tracer diffusivity is inversely proportional to a fractional power of the viscosity of the solvent instead. This fractional power dependence of viscosity on diffusion is often referred to in the literature as the fractional Stokes-Einstein (FSE) relation, (D 12 /T) ∝ η −t , where t is known to be normally less than unity and generally around 2/3.…”
Section: B Solvent Dependencementioning
confidence: 99%
“…As the chain length (and viscosity) of the n-alkanes increased, the value of r for O 2 from eq 1 became smaller, 4 i.e., the diffusion of O 2 became progressively faster than predicted by a constant molecular "size." A possible explanation is that the n-alkanes, which on average are relatively extended, provide regions of increasing length in which the interactions between O 2 and the hydrocarbon are relatively weak and through which diffusion is relatively rapid.…”
Section: Introductionmentioning
confidence: 97%